Non-dioxin-like polychlorinated biphenyls induce a release of arachidonic acid in liver epithelial cells: a partial role of cytosolic phospholipase A(2) and extracellular signal-regulated kinases 1/2 signalling - Umannová, Lenka; Neča, Jiří; Andrysík, Zdeněk; Vondráček, Jan; Upham, B. L; Trosko, J. E; Hofmanová, Jiřina; Kozubík, Alois; Machala, Miroslav (Toxicology, 2008)
Non-dioxin-like polychlorinated biphenyls (NDL-PCBs) have been shown to act as tumor promoters in liver; however, the exact mechanisms of their action are still only partially understood. One of the interesting effects of NDL-PCBs is the acute inhibition of gap junctional intercellular communication (GJIC), an effect, which has been often found to be associated with tumor promotion. As previous studies have suggested that NDL-PCB-induced disruption of lipid signalling pathways might correspond with GJIC inhibition, we investigated effects of PCBs on the release of arachidonic acid (AA) in the rat liver epithelial WB-F344 cell line, a well-established model of liver progenitor cells. We found that both 2,2',4,4'-tetrachlorobiphenyl (PCB 47) and 2,2',4,4',5,5'-hexachlorobiphenyl (PCB 153), but not the dioxin-like, non-ortho-substituted, 3,3',4,4',5-pentachlorobiphenyl (PCB 126), induce a massive release of AA. The AA release, induced by PCB 153, was partially inhibited by extracellular signal-regulated kinases 1/2 (ERK1/2) signalling inhibitor, U0126, and by cytosolic phospholipase A(2) (cPLA(2)) inhibitor, AACOCF(3). Although PCB 153 induced both ERK1/2 and p38 activation, the specific p38 kinase inhibitor, SB203580, had no effect on AA release. Inhibitors of other phospholipases, including phosphatidylcholine-specific phospholipase C or phosphatidylinositol-specific phospholipase C, were also without effect. Taken together, our findings suggest that the AA release, induced by non-dioxin-like PCBs in liver progenitor cell line, is partially mediated by cytosolic PLA(2) and regulated by ERK1/2 kinases. Our results suggest that more attention should be paid to cell signalling pathways regulated by AA or eicosanoids after PCB exposure, which might be involved in their toxic effects.
Keywords: Liver; financování organizované; Animals; buněčné linie; Stem Cells; Polychlorinated Biphenyls; játra; Phospholipases A2, Cytosolic; mitogenem aktivovaná proteinkinasa 3; polychlorované bifenyly; Rats, Inbred F344; Epithelial Cells; mitogenem aktivovaná proteinkinasa 1; cytosolické fosfolipasy A2; kmenové buňky; signální transdukce; Signal Transduction; Cell Line; Financing, Organized; kyseliny arachidonové; Environmental Pollutants; Mitogen-Activated Protein Kinase 3; potkani inbrední F344; Arachidonic Acids; krysa rodu Rattus; zvířata; látky znečišťující životní prostředí; Mitogen-Activated Protein Kinase 1; epitelové buňky; Rats